Degradation of forest and biodiversity in Sariska National Park, India and the responsible factors. (2015) - De, Utpal Kumar; Chauhan, Krishna
Sariska Tiger Reserve has been in the limelight due to the extinction of its prime species tiger. It is a serious matter of concern to maintain the erstwhile rich biodiversity of the reserve. Due to illegal poaching and extensive pressure from the villagers for grazing and various forest products, man animal conflict has been growing and leading to the degradation of forest and its bio-diversity. Thus, efforts are on through reintroduction of a few tigers in the park from other forest area and gradual relocation of families from the core areas to control the degradation of pristine forest and its bio-diversity along with the improvement of the situation. This paper tries to examine the nature of degradation of forest and bio-diversity of Sariska Tiger Reserve. In addition, the reasons for the degradation have been analysed with the help of collected primary data and available secondary information.